Book Review - Shmiher, Taras (East European Journal of Psycholinguistics, 2018)
UKRAINIAN TRANSLATION WORKSHOP IN PRIASHIVUkrajinský jazyk a kultúra v umeleckom a odbornom preklade v stredoeurópskom priestore : Zbornik príspevkov z medzinárodného vedeckého seminára, ktorý sa konal dňa 27.9.2017 na Katedre ukrajinistiky Inštitutu ukrajinistiky a stredoeurópskych štúdií Filozofickej fakulty Prešovskej univerzity / Filozofická fakulta Prešovskej univerzity v Prešove ; ed.: Jarmila Kredátusová. Prešov: Filozofická fakulta Prešovskej univerzity v Prešove, 2018. 216 p. (Opera Translatologica; 6/2018). Ukrainian modern academic traditions in the Western Transcarpathian area of Priashiv (Presov in Slovak) go back to the 19-century intellectual institutions of the Ukrainian Catholic Church of the Byzantine Rite. After WW2, the main centre of Ukrainian education was the Pegagogical College which was later transformed into a separate university. This university helps the local Ukrainians maintain and develop their rich traditions of learning and research. It is no surprise that the very university hosted the International academic workshop “The Ukrainian Language and Culture in the Literary and Sci-Tech Translation of Middle European Space” (27 September 2017). The workshop brought together specialists in Ukrainian Studies from Ukraine, Slovakia, Czechia and Poland. One year later the conference volume was finalized and published.The first part of the book contains the historical and bibliographical essays which record the history of Ukrainian-Slovak and Ukrainian-Czech literary translation. Jarmila Kredátusová’s task was to present the outline of Slovak-Ukrainian and Ukrainian-Slovak translation which started progressing rather dynamically only after WW2. She presents its history divided into decades and discusses specific features and some statistical data from each period. In the end, she also describes today’s hardships of this translation in Slovakia (relations with readership, translation criticism, professional qualification) which are similar to ones in Ukraine. The history of Ukrainian-Czech translation is longer and richer. The existing extended papers cover the pre-1989 time rather well, that is why Rita Lyons Kindlerová and Iryna Zabiyaka dedicated their articles to the editions and tendencies of the recent decades. Rita Lyons Kindlerová offers the analysis of translated literature from Ukrainian into Czech and pinpoints the turning moment of the year 2001 when Ukrainian literature started reentering Czech society and have promising prospects among readers. Conversely, Iryna Zabiyaka studies the literary presentation of Czechia in Ukraine and considers the most important translations and main tendencies. She also designs a list of Czech authors whose writings are worth translating into Ukrainian. At the same time, she characterizes the pitfalls of Ukraine’s translation market from the viewpoint of these translations. Since we lack translation bibliographies and insightful translation monographs, the above articles contribute to a larger possible publication in future which will reveal more sociological dimensions of Ukrainian-Slovak and Ukrainian-Czech translation.Papers in the second part focus on literary translation. Liudmyla Siryk outlined similarities in the translation theories of Mykola Zerov and Maksym Rylskyi. Thus, she has proven that Rylskyi’s views were the further progress of Zerov’s ones, and we have to remember it may be a gesture of respect or substitution: Zerov was murdered in 1937, and Rylskyi fulfilled his duty to preserve and develop the fundamental ideas of his friend and colleague. Anna Choma-Suwała explored the facets of literary interpretations and connections between Oleh Olzhych (Kandyba) and Józef Łobodowski. Łobodowski’s translations did not only discover the intellectual poetry by Oleh Olzhych, but they are also a contribution to the Polish-Ukrainian cultural contacts and cooperation. Yuliya Yusyp-Yakymovych addresses to verse translation by investigating the specific features of rendering intonation, rhythm, meter, repetitions, onomatopoeia and aesthetic norms in translation. Adriana Amir’s contribution deals with the Slovak-language translation of Vasyl Shkliar’s historical novel ‘The Black Raven’ (done by Vladimír Čerevka) and tackles the issues of reflecting lexical means for showing the real historical context which border on the shaky axiological limits of political correctness. The main aesthetic form of contemporary writing is the usage of non-standard language which is abundant in modern Ukrainian literature. That is why Veronika Dadajová regarded incorrect figures of the literary sociolect as a topical point of literary translation nowadays. Meanwhile, Viera Žemberová interprets Yuriy Andrukhovych’s literary and aesthetic experience for Slovak readers by analyzing his novel ‘Recreations’ whose Slovak translation was published in Priashiv in 2003.Sci-tech translation is focused on in the third part containing articles on rendering terms and grammatical problems of interlingual translation. The paper by Mária Čižmárová will serve as a practical tool for Ukrainian-Slovak translators and interpreters who will have to render idioms with the floristic component. Similarly practical are the contributions covering two branches of Ukrainian-Slovak specialized translation: commercial translation (by Lesia Budnikova and Valeriya Chernak) and legal translation (by Jarmila Kredátusová and Valeriya Chernak). The study of loan words is the topic of the paper by Jana Kesselová which offers the complex view of loan processes in today’s Slovak. However, it would be desirable to discuss Ukrainian sources as well. It is rather a rare case when one volume consists of papers discussing both literary translation and sci-tech translation, but in the presented book, this amalgamation is quite natural and shows the multifacetedness of Ukrainian translation in Slovakia.The informational contents of all the papers are rather high, and they will be useful for practical research by scholars, translators and critics. The good balance of early ‘classical’ and recent publications creates a complete picture both of the coverage of the topic in the chronological dynamics and the presentation of the academic traditions of institutions where the papers were produced.This conference volume is an important contribution to Ukrainian Translation Studies in the area of Priashiv which has been shaped and developed by the publications in the literary magazine ‘Dukla’ (published since 1953), the proceedings of the Cultural Union of Ukrainian Workers (‘Naukovi zapysky KSUT’ in the 1980s to the early 1990s) and other editions of the Ukrainian Division of the Slovak Pedagogical Publishing House. The book will be useful for really wide readership in academic, literary and professional communities.